2-Aryl-Benzoimidazoles as Type II NADH Dehydrogenase Inhibitors of Mycobacterium tuberculosis - Saha P.; Sau S.; Kalia N.P.; Sharma D.K. (My University, 2025)
The nonproton pumping type II NADH dehydrogenase in Mycobacterium tuberculosis is essential for meeting the energy needs in terms of ATP under normal aerobic and stressful hypoxic environmental states. Type II NADH dehydrogenase conduits electrons into the electron transport chain in Mycobacterium tuberculosis, which results in ATP synthesis. Therefore, the inhibition of NDH-2 ensures the abolishment of the entire ATP synthesis machinery. Also, type II NADH dehydrogenase is absent in the mammalian genome, thus making it a potential target for antituberculosis drug discovery. Herein, we have screened a commercially available library of drug-like molecules and have identified a hit having a benzimidazole core moiety (6, H37Rv mc26230; minimum inhibitory concentration (MIC) = 16 μg/mL and ATP IC50 = 0.23 μg/mL) interfering with the oxidative phosphorylation pathway. Extensive medicinal chemistry optimization resulted in analogue 8, with MIC = 4 μg/mL and ATP IC50 = 0.05 μg/mL against the H37Rv mc26230 strain of Mycobacterium tuberculosis. Compounds 6 and 8 were found to be active against mono- and multidrug-resistant mycobacterium strains and demonstrated a bactericidal response. The Peredox-mCherry experiment and identification of single-nucleotide polymorphisms in mutants of CBR-5992 (a known type II NADH dehydrogenase inhibitor) were used to confirm the molecules as inhibitors of the type II NADH dehydrogenase enzyme. The safety index >10 for the test active molecules revealed the safety of test molecules. © 2024 American Chemical Society.